Catastrophe mechanism and classification of discontinuity behavior in thermal science (I): Fold catastrophe - Xie, Zhikang; Fan, Weicheng; Wang, Qing’an (Chinese science bulletin, 2000)
O4; The mechanism of discontinuity behavior has important significance in the study of thermal science,such as fire,combustion,explosion and heat transfer.This sort of discontinuity behavior and the catastrophe caused by system nonlinearity may be equivalently classified according to the catastrophe model promulgated by catastrophe theory.Under the conditions of uniform temperature and thermal isolation,the self-ignition behavior of a Semenov System can be viewed as a result of the fold catastrophe of the system.